Average age at last live birth in 'lucky few' and 'late baby boom' birth cohorts in the United States. Issue 3 (2nd September 2017) - Siordia, Carlos; Leyser-Whalen, Ophra
ABSTRACT: The quantum, tempo, and characteristics of population fertility can change rapidly between birth cohorts. Understanding secular trends in fertility behavior can help inform research concerned with family and health policy. The current investigation is novel in that it uses 'intersectional markers of social stratification' with a large sample of women to examine if the average age at last live birth shifted between two birth cohorts. The analysis uses 41, 884 observations from the 1990 Decennial 1% Public Use Microdata Sample (PUMS) file to capture the fertility behavior of lucky few (LF) women (born 1936–1945) and 72, 489 observations from the 2010 American Community Survey PUMS file to capture the fertility behavior of late-baby boom (LBB) women (born 1956–1965). The investigation provides empirical evidence that the average age at last live birth decreased in LBB women compared to LF women.